HUBUNGAN TINGKAT KECUKUPAN BESI DENGAN KADAR HEMOGLOBIN PADA REMAJA HAMIL USIA 15-19 TAHUN (Studi di Kelurahan Rowosari Kota Semarang Tahun 2016) - Putri Sriwulandari Pangestika; Martha Irene Kartasurya; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Adolescent pregnancy has a higher risk for anemia due to the growth of adolescent mothers. Teen girls tends to limits their food consumption thus increasing the risk of anemia. The number of adolescent pregnancies in Puskesmas Rowosari working area was higher than other Puskesmas in Semarang.This study was aimed to analyze the correlation between the adequacy rate of iron and hemoglobin levels of pregnant teenagers aged 15-19 years old.This study was an explanatory research with a cross sectional approach.The population was pregnant teenagers aged 15-19 years old in Rowosari Village, Semarang.Total sampling method was used to choose 44 pregnant teenagers.Data were collected through interviews using a structured questionnaire. Data analysis was done by Pearson, Spearman Correlation , and Chi Square tests.The result showed that the average of hemoglobin level of (11.27±0.65) g/dL, the total iron adequacy rates was (59.1±17,25)%, heme iron (70.5±18,60)%, non-heme iron (53.2±10,96)%, protein (50,0%±24,88)%, vitamin C (63.3±41,65)%, folic acid (59.1±4,78)% fall under insufficient category.The adequacy level of energy were (79.5±8,55)% and vitamin A were (56.3±43,24)%. The non compliance rate of iron tablet consumption was 63.6%.There was a correlation between adequacy rate of iron and hemoglobin levels (p=0,046).There was no correlation between adequacy rate of heme iron, non-heme iron, energy, protein, vitamin A, vitamin C, folic acid, the compliance of iron tablet consumption and hemoglobin levels. It was concluded that adequacy rates of total iron consumption and hemoglobin levels. It is suggested that pregnant women need to increase the consumption of food combination which contains iron such as meat and fish also vegetables.